Genealogi Konsep Wasatiyyah dalam Pemikiran Islam Klasik dan Kontemporer - Khoirin, Lukman; Sugito; Faizin, Khoirul (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
This study traces the genealogy of wasatiyyah (Islamic moderation) from the classical to the contemporary era, analyzing the evolution of its meaning and application within the Islamic intellectual tradition. Employing a qualitative approach with a library research design, data was gathered through content analysis of works by prominent scholars and thinkers from various periods. Findings indicate that in the classical era, wasatiyyah was understood as an ethical-theological balance in creed and worship, reflected in the thoughts of Al-Ghazali and Ibn Taymiyyah. In the modern era, the concept transformed into a principle of social and intellectual reform and ijtihad (independent reasoning) in response to Muslim decline and the challenges of modernity, as represented by Muhammad Abduh and Rashid Rida. In the contemporary era, wasatiyyah has evolved into a pluralistic ideology rejecting extremism, emphasizing tolerance and social harmony, with Yusuf Al-Qaradawi and Nusantara Islam figures like Nurcholish Madjid and Abdurrahman Wahid as its exponents. This evolution confirms that wasatiyyah is an inherent adaptive mechanism within Islamic thought, enabling the religion to remain relevant and contribute constructively across diverse historical contexts. The study's implications highlight the historical legitimacy of wasatiyyah in promoting religious moderation today, and the importance of a multidimensional approach to its implementation.